2017
DOI: 10.1038/ncomms14740
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of delta-secretase improves cognitive functions in mouse models of Alzheimer’s disease

Abstract: δ-secretase, also known as asparagine endopeptidase (AEP) or legumain, is a lysosomal cysteine protease that cleaves both amyloid precursor protein (APP) and tau, mediating the amyloid-β and tau pathology in Alzheimer's disease (AD). Here we report the therapeutic effect of an orally bioactive and brain permeable δ-secretase inhibitor in mouse models of AD. We performed a high-throughput screen and identified a non-toxic and selective δ-secretase inhibitor, termed compound 11, that specifically blocks δ-secret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
89
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 109 publications
(97 citation statements)
references
References 50 publications
3
89
0
Order By: Relevance
“…Interestingly, knockdown of AEP in DMSO controls resulted in increased α‐Syn levels, and MAO‐B enzymatic activity tightly associated with α‐Syn N103 fragmentation, but not total α‐Syn levels (Fig D–F), indicating that α‐Syn N103 might be responsible for promoting MAO‐B enzymatic activity. We made similar observations with small molecular AEP inhibitors, compound 11 and MVO (van Kasteren et al , ; Zhang et al , ), which inhibited α‐Syn N103 production triggered by MPP + . As expected, AEP enzymatic activity was inhibited by these two compounds.…”
Section: Resultssupporting
confidence: 82%
“…Interestingly, knockdown of AEP in DMSO controls resulted in increased α‐Syn levels, and MAO‐B enzymatic activity tightly associated with α‐Syn N103 fragmentation, but not total α‐Syn levels (Fig D–F), indicating that α‐Syn N103 might be responsible for promoting MAO‐B enzymatic activity. We made similar observations with small molecular AEP inhibitors, compound 11 and MVO (van Kasteren et al , ; Zhang et al , ), which inhibited α‐Syn N103 production triggered by MPP + . As expected, AEP enzymatic activity was inhibited by these two compounds.…”
Section: Resultssupporting
confidence: 82%
“…22 Following confirmatory assays with purified AEP, we identified top hits and subsequent triaging produced a lead compound, termed compound 38 . A kinetic analysis of the small-molecule inhibitor indicated that compound 38 competitively inhibits AEP activity strongly, K I = 105 ± 37 nM (Figure 1A,B).…”
Section: Resultsmentioning
confidence: 99%
“…22 However, its Caco-2 cell permeability was minimal, suggesting that the compound may not be readily absorbed upon oral administration 23 (Table 1). …”
Section: Resultsmentioning
confidence: 99%
“…Sheddases and the relevant substrates are consequently considered as drug targets. A key example is an excessive level of shed TNFa, Zhang et al (2017Zhang et al ( , 2015 The table lists selected examples where the pathological role of a sheddase or its substrate to a disease has been established in animal models and through human genetics. The many instances where altered sheddase expression only correlates with disease are not listed.…”
Section: Disease Association and Shedding-based Drugsmentioning
confidence: 99%